The Effect of GRDP, Minimum Wages, and Education on Workforce Absorption in Regencies and Cities in East Java - Ruslan, Widya Devina Amelia Putri; Devanto Shasta Pratomo (Journal of Development Economic and Social Studies, 2025)
Workforce absorption is the number of jobs filled, reflected in the large number of working people. The absorption of the population into work caused by the large demand for labor. Therefore, workforce absorption can be said to be the demand for labor. This research aims to determine the influence of GRDP, Minimum Wage, and Education on Workforce Absorption in Regencies and Cities of East Java Province in 2017-2020. The method used is a quantitative method using Eviews as a tool for testing data. The results of this research can be concluded that GRDP (X1) has a positive and insignificant effect on workforce absorption, Minimum wage (X2) has a positive and significant effect on workforce absorption, and Education (X3) has a positive and significant effect on workforce absorption.